Time domain parameter identification of transient electromechanical oscillations. Issue 2 (16th January 2019) - Sotelo-Castañón, Julián; Gutiérrez-Robles, José Alberto; Johnson, Brian; Moreno, Pablo; Guzman, Armando
Abstract : Purpose: The power systems behavior is nonlinear, and this is reflected in that the measurement signals are composed by multi-components. Thus, this paper aims to present a method for analyzing multi-component signals that allow calculating signal parameters such as frequency, damping constant, amplitude and phase for each component, as well as determining the direct current component. Design/methodology/approach: The method proposed is based in the Z-transform of a damped sinusoidal signal with direct current. Only the Z-transform poles are used to form equation systems which are used to obtain frequency and damping. Then, the amplitude, the phase and the direct current component are determined by the above results. Findings: The method is able to determine frequencies, damping constants, phases and amplitudes of the different modal components of a signal using only a few measurements. Moreover, the method does not require filter banks tuned with some previous knowledge of signal's characteristics. The presented test cases of field measured signals show the good performance of the proposed method, which is able to obtain the parameters of interest with a very short observation window. Originality/value: One quality of this method is that it has a very short delay to reach the first solution and from there you get one result each sample; the delay time is equivalent to 2 + 4C samples where C is the number of components in the signal. Finally, it is concluded that because of the small number of samples that are needed and the low algorithmic complexity of the methodology, the method is apt to make applications in real time.